The Political Behavior Of Middle School Students And The Formation Of Their Political Trends - et. al., Qais Ismaiel jabbar al challabi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The political behavior of the human being is part of his existence; Whereas, all the emotions, reactions, attitudes and judgments made by community members regarding a topic or issue that concern their lives and social relations, explain the resulting political behavior towards all public issues. As a result, attention must be paid to all the stances and rulings issued by the components and individuals of society regarding political life. The general public and society, and the leaderships and ruling political parties should respond to the behavior and political positions of the majority of the community members, and this stage (the preparatory stage) must be taken care of by the government and civil society institutions and in cooperation with school administrations in order to preserve respect for the principle of legitimacy, and to consecrate the principle of peoples' trust in the rulers and the ruling authorities Generally.